Assessment of Risk Factors for Nutritional Rickets in Children Aged 6–59 Months at A County Referral Hospital in Kenya - ORINA, Louisa; CHEGE, Peter; WALEKHWA, Michael (African Journal of Nutrition and Dietetics, 2025)
Nutritional rickets remains a major child health challenge in low- and middle-income countries, including Kenya. Beyond undernutrition, socio-demographic disadvantage, inadequate calcium and vitamin D intake, and limited sunlight exposure contribute to its persistence. This study assessed the nutritional status of children aged 6–59 months attending Murang’a County Referral Hospital (MCRH) and examined associated risk factors for nutritional rickets. An analytical cross-sectional study was conducted among 212 children aged 6–59 months visiting MCRH. Anthropometric data were converted to Z-scores using World Health Organization standards for classifying stunting, underweight, and wasting. Clinical and biochemical tests were used to confirm rickets diagnosis. Data on socio- emographic, dietary, and sunlight exposure were collected using a structured questionnaire. Associations were tested using chi-square and multivariable logistic regression at p < 0.05. Of the 212 children, 26 (12.3%) had nutritional rickets. Prevalence was highest among wasted (50.0%), stunted (41.2%), and underweight (40.0%) children, compared to 6.8% of those with normal nutrition. Logistic regression showed that stunting (AOR = 3.00, 95% CI: 1.25–7.20), underweight (AOR =2.46, 95% CI: 1.10–5.50), and wasting (AOR = 2.72, 95% CI: 1.05–6.99) were independently associated with rickets. Additional predictors included younger age (6–24 months), low maternal education (AOR = 3.32, 95% CI: 1.68–6.56), inadequate calcium intake (AOR = 2.40, 95% CI: 1.78–5.28), inadequate vitamin D intake (AOR = 3.00, 95% CI: 1.45–6.33), low dietary diversity (AOR = 2.23, 95% CI: 1.12–4.44), and limited sunlight exposure (<20 minutes/day) (AOR = 2.59, 95% CI: 1.31–5.11). Nutritional rickets in Murang’a hospital is multifactorial, associated with undernutrition, socio-demographic vulnerabilities, poor dietary intake, and inadequate sunlight exposure. Integrated prevention strategies, including food fortification, vitamin D supplementation, maternal education, and community campaigns on safe sun exposure, are essential to reduce rickets burden among children 6-59 months.